PSVIII-14 Impact of altering Lys:energy ratio during gestation on offspring post-wean growth performance. (30th November 2020) - Bruhn, Tiffany; Frobose, Hyatt; Levesque, Crystal L
Abstract: Lysine and energy supply in gestation can influence preweaning mortality and sow lactation feed intake but little data exists for the impact on offspring post-weaning performance. A study evaluated the effects of dietary Lys:energy during gestation on offspring performance from weaning until market. Both primiparous and multiparous females (n=59 in 2 groups) were blocked by parity, balanced by weight and allotted to one of three gestation feeding regimens: 1.50 g SID Lys/Mcal ME (Control), 1.50 g SID Lys/Mcal ME from d2–89 and 2.11 g SID Lys/Mcal ME from d90–110 d of gestation (PF1) and 1.25, 1.07, and 0.88 g SID Lys/Mcal ME from d2–89 for gilts, parity 1 and parity 2+, respectively and 2.11 g SID Lys/Mcal ME from d90–110 d of gestation (PF2). Offspring (n=682) were weaned into 40 pens by maternal treatment (n=13-15 pigs/pen, mixed gender/pen). Pen feed disappearance and individual pig weights were determined at least once each month until market. Animals were marketed by a technician blinded to treatment; to account for potential marketing bias, adjusted d130 weight was calculated. Data were analyzed as a randomized complete block with means separation using Scheffe's adjustment. The offspring of Control sows had decreased BW at weaning (P < 0.001) versus PF1 offspring and Control offspring had decreased BW (P = 0.001) compared to both PF1 and PF2 at d7 post-weaning. Despite minimal differences in ADG, ADFI, or G:F between treatments, PF2 offspring were heavier (P = 0.02) at market and adjusted d130 weight than Control pigs. While PF1 offspring had similar BW at market than Controls, they spent fewer (138.2 vs. 142.7; P = 0.009) days on feed than Control pigs due to the aforementioned marketing bias. Altered Lys:energy ratio in a single gestation cycle improved offspring post-wean performance.